Design Of A Web-Based Archive Warehouse Management Information System In Improving The Efficiency Of Archives Management - Rusli Mardianto; Jeki Armentaria (CV. AFDIFAL MAJU BERKAH, 2026)
The development of information technology has significantly contributed to enhancing knowledge quality and operational efficiency within organizations. The use of the internet provides a rapid and comprehensive means to obtain and disseminate information in both the public and private sectors. However, many repositories still rely on manual archive management methods, which often face various challenges, such as lengthy archive search times, difficulty in locating archives, and delays in the decision-making process. This problem is further complicated by the large number of archives and uncertainty regarding archive organization and storage locations. Therefore, a web-based archive information management system is needed to address these challenges. This study aims to design and develop a web-based archive information management system to enhance archive management efficiency and facilitate archive search through integrated data management in a single location. The research method employed is Research and Development (R&D), encompassing needs analysis with problem identification, design of a web-based system prototype, implementation of key functions, and system evaluation through functionality testing. Data were collected through direct observation. The research results indicate that implementing the web-based archive information management system can improve document management accuracy and accelerate archive search processes. Additionally, the system supports simultaneous collaboration among users. For example, a comparison between conventional archive management methods and the web-based system demonstrates a significant improvement in effectiveness. It is concluded that a web-based information management platform for archive repositories is a viable alternative to address issues related to archive administration, document search, and to enhance the ability to make faster and more accurate decisions, as well as optimize the use of organizational assets.